Results pathomorphologic study of musculocutaneous tissue samplings with people who subject to influence a little doses of ionizing radiation - Ya. V. Porovsky; V. V. Nedosekov; A. I. Ryzhov; F. F. Tetenev (Бюллетень сибирской медицины, 2010)
To study the influence of small doses of ionizing radiation on microvasculature, the skin-muscular biopsy in the lower leg region was performed in 33 liquidators or clean-up workers at the Chernobyl Nuclear Power Plant and 7 workers of a typical research nuclear reactor (RNR).A histological feature in the liquidators was the presence of the disseminated productive panvasculitis with pronounced lymphocytary infiltration of the vessel wall and sclerosis outcome in most microvasculature vessels, perivascular sclerosis. Changes in vessels of RNR workers increased with the increase а total doses from productive panvasculitis with involvement from few to most microvasculature vessels, formation of perivascular fibrosis and perivascular sclerosis. The revealed changes may be significant in the observed somatic pathology.